Health Counseling and Physical Examination, Blood Pressure, Blood Sugar and Free Treatment at the Hibas Primary Clinic, Simalungun Regency - Purba, Yeni Trisna; Pakpahan, Romauli; Butar-Butar, Doortua; Friani, Sri Rahma; Erhan, Keysha Iszmi; Adelia, Adelia; Wijaya, Imroatulhuda; Abednego, Danuarta Azarya (PT Inovasi Pratama Internasional, 2024)
The community service program,